Teaching higher-order thinking in social studies: The role of content coverage and intellectual challenge - Aashamar, Peter Nicolai; Klette, Kirsti; Christensen , Anders Stig (JSSE - Journal of Social Science Education, 2024)
Purpose: The study aimed at investigating the prevalence and characteristics of classroom practices geared at promoting higher-order social studies thinking, and the potential dilemma for teachers between focusing on explaining knowledge to and intellectually challenging students. Design/methodology/approach: A comparative design using data from naturalistic classroom observations of 80 social studies lessons in Denmark, Norway, and Sweden. We deployed the PLATO observation system to systematically measure intellectual challenge and the conceptual complexity of teacher explanations across the three countries. Findings: We found evidence that many teachers promoted higher-order thinking to varying degrees within and across the three countries. Furthermore, Danish, Norwegian, and Swedish teachers seemed to focus on different teaching practices related to higher-order thinking. Practical implications: These findings provide important empirical knowledge about naturally occurring classroom practices in the Nordic context that may be relevant for teachers to reflect on higher-order thinking in social studies.